NF-κB and TNF-α Expressions and Histological Image of White Rat’s, Rattus norvegicus, Ileum With Indomethacine-Induced IBD (Inflammatory Bowel Desease) After Mas Ngur Oyster (Atactodea striata) Extract Therapy - Dullah Irwan Latar; Celcius Waranmaselembun; Yuliana Anastasia Ngamel; Abu Samad Serang; Anna Kartika Ngamel (Green Publisher Indonesia, 2023)
Inflammatory disease in gastric tract called Inflammatory Bowel Disease (IBD), particularly colon, in general, results from the use of non-steroid anti-inflammatory drug, such as indomethacine. The use of natural material, such as mas ngur oyster (Atactodea striata) as traditional medicine has been long known by people in Kei Islands–Southeast Mallucas. This study is aimed at measuring the ability of active compounds of this oyster extract in reducing NF-κB and TNF-α expression and showing the histological image of indomethacine-induced rat ileum with IBD after treatment with mas ngur oyster extract. It used 8-12 week old male rats (Rattus norvegicus) of 150 - 200 g BW. The rats were divided into 3 groups, healthy group, sick group (induced with 15 mg/kg BW of indomethacine), and treatment group (orally induced with indomethacine at a dose of 15 mg/kg BW then treated with mas ngur oyster extract at the dose of 100, 400, 700 mg/kg BW). Indomethacine induction at the dose of 15 mg/kg BW and mas ngur oyster extract therapy were orally administered. NF-κB and TNF-α expressions were measured using immunohistochemicals, and the histological image used Hematoksilin-Eosin staining. Results showed that extract therapy gave significant effect (P<0.05) at the effective dose of 400 mg/kg BW that could reduce 86.421% of NF-κB expression and 60.972% of TNF-α expression in the rat ileum and result in tissue recovery of the IBD rat’s ileum after the therapy.